HATs meet structural biology. (June 2022) - Rullo-Tubau, Josep; Bartoccioni, Paola; Llorca, Oscar; Errasti-Murugarren, Ekaitz; Palacín, Manuel
Abstract: Heteromeric amino acid transporters (HATs) are one of the ten types of amino acid transporters present in the human body. Growing interest in the pathophysiological role of this group of transporters in rare and complex diseases and cancer has brought about the recent resolution of various structures of human HATs and bacterial homologues at atomic level. This knowledge sheds light on the mechanisms of transport used by these molecules. Here, we discuss the molecular bases underlying substrate specificity, binding asymmetry, and the impact of disease-causing mutations on transporter biogenesis and function.